Entrevista a Alberto Benavides Ganoza, filósofo, escritor y agricultor - Gutiérrez, Sha Sha (2024)
Alberto Benavides Ganoza (Lima, 1949), philosopher, writer, educator, cultural promoter and farmer. Creator and manager of the Samaca farm, 75 kilometers from Ica, crossing the Ocucaje desert. Founder and director of the Abraham Valdelomar Library in Huacachina, well known for the literary and cultural activities it organizes periodically. Disseminator of Peruvian culture, particularly the literature of the Ica region. He is the author of the poetry books Cantos de puerto Huamaní (1997), Alto espionaje (2013) and Al pie del desierto (2016) and of various essays and journalistic texts including El ave huida. Ensayos de filosofía (1979). In the following interview with Espinela, he tells us about the reasons that led him to leave the city of Lima to settle in the countryside, in the middle of the Ica desert; the challenges of his agricultural work on the farm he himself created; the relationship between education, literature and nature; some aspects of his creative work as a writer, and the mysticism that human beings should not forget in their connection with the natural world.